Secondary hemophagocytic lymphohistiocytosis in a child with Sickle Cell Anemia and Hepatitis A and Hepatitis E co-infection: A case report - Govind Choudhary; Nida Mirza; Swati Patel (Elsevier, 2024)
Background: Secondary hemophagocytic lymphohistiocytosis (HLH) is a potentially fatal condition commonly triggered by infections. HLH secondary to hepatitis E or hepatitis A and E coinfection has been scarcely reported. Diagnosing HLH in sickle cell anemia can be tricky. Case report: We present a 10-year-old boy, a known case of sickle cell anemia, who presented with acute viral hepatitis (HAV and HEV IgM positive). He initially improved with supportive management. However, on the fifth day of illness, he developed fever, tachypnea, and pancytopenia. Inflammatory markers, including serum ferritin, triglycerides, and D-dimer were raised. Bone marrow examination revealed hemophagocytosis. A diagnosis of sickle cell disease with HAV and HEV coinfection with secondary HLH was made. The patient responded to steroids and was well on follow-up after 3 months. Conclusion: HAV and HEV coinfection with a background of sickle cell anemia with secondary HLH is very rare. Diagnosis of HLH in sickle cell anemia is challenging. Timely diagnosis and management of secondary HLH are vital for a favorable outcome.